MEDIA AND THE CONSTRUCTION OF REALITYHOW "SAVORY" ARE LOBSTER SEEDS AS AN EVENT FOR CORRUPTION (FRAMING ANALYSIS STUDY OF TRANS7 AFTERNOON EDITORIAL NEWS) - Bahniati; Tina Kartika, Andy Corry Wardhani, Abdul Firman Ashaf (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The arrest of Minister Edhy Prabowo occurred in the early hours of Wednesday 25 November 2020 at Soekarno-Hatta Airport by the KPK. This attracted the attention of online media including the Trans7 Afternoon Editorial Board. The research problem studied is how Trans7 constructs the reality of Edhy Prabowo's arrest at Soekarno-Hatta Airport and the frames that appear in its reporting. Knowing the construction of Trans7 is important because it is a powerful media that has editorial autonomy. The research uses qualitative methods through Pan & Kosicky's framing analysis model. The results show that Trans7 sees Edhy Prabowo as an OTT suspect by the KPK. The news structure studied is the framing element; schematic, script, thematic and rhetorical. Schematic; Trans7 linked the suspect to the alleged bribery case with foreign parties (San Francisco). The main source of the news is the Corruption Eradication Commission (KPK). The background information that emerged was an alleged bribery case that occurred overseas (San Francisco). Script; Trans7 positions the information covered as complementary and completely conveyed. Thematic; Trans7 believes that the suspect is connected to a local network, Edhy is suspected of being involved. Rhetorically; Trans7 provides apposition and text emphasis on graphic elements.